Exercise therapy, education, and cognitive behavioral therapy alone, or in combination with total knee arthroplasty, in patients with knee osteoarthritis: a randomized feasibility study - Turid Rognsvåg; Ingvild Buset Bergvad; Ove Furnes; Kari Indrekvam; Anners Lerdal; Maren Falch Lindberg; Søren T Skou; Jan Stubberud; Mona Badawy (Pilot and Feasibility Studies, 2024)
Abstract Background One in five patients experience chronic pain 1 year after total knee arthroplasty (TKA), highlighting the need for enhanced treatment strategies to improve outcomes. This feasibility trial aimed to optimize the content and delivery of a complex intervention tailored to osteoarthritis (OA) patients at risk of poor outcome after TKA and assess the feasibility of initiating a full-scale multicenter randomized controlled trial (RCT). Methods Patients scheduled for TKA were included between August 2019 and June 2020 and block-randomized into one of three groups: (a) 12-week exercise therapy and education (ExE) and 10-module internet-delivered cognitive behavioral therapy (iCBT), (b) TKA followed by ExE and iCBT and (c) TKA and standard postoperative care. Outcomes were (i) recruitment and retention rate, (ii) compliance to the intervention and follow-up, (iii) crossover, and (iv) adverse events, reported by descriptive statistics. Results Fifteen patients were included in the study. Only 1 out of 146 patients screened for eligibility was included during the first 4 months. During the next 3 months, 117 patients were not included since they lived too far from the hospital. To increase the recruitment rate, we made three amendments to the inclusion criteria; (1) at-risk screening of poor TKA outcome was removed as an eligibility criterion, (2) patients across the country could be included in the study and (3) physiotherapists without specific certification were included, receiving thorough information and support. No patients withdrew from the study or crossed over to surgery during the first year. Nine out of 10 patients completed the ExE program and six out of 10 completed the iCBT program. Fourteen out of 15 patients completed the 1-year follow-up. One minor adverse event was registered. Conclusions Except for recruitment and compliance to iCBT, feasibility was demonstrated. The initial recruitment process was challenging, and necessary changes were made to increase the recruitment rate. The findings informed how a definitive RCT should be undertaken to test the effectiveness of the complex intervention. Trial registration The MultiKnee RCT, including the feasibility study, is pre-registered at ClinicalTrials.gov: NCT03771430 11/12/2018.